Cloud computing : concepts, technology, & architecture - Erl, Thomas; Puttini, Richardo; Mahmood, Zaigham (United States Arcitura education Inc., 2013)
Breaks down proven and mature cloud computing technologies and practices into a series of well-defined concepts, models, technology mechanisms, and technology architectures, all from an industry-centric and vendor-neutral point of view. In doing so, the book establishes concrete, academic coverage with a focus on structure, clarity, and well-defined building blocks for mainstream cloud computing platforms and solutions.
Includes index.
oif 12/06/15
Loan
Keywords: Cloud computing; Cloud mechanisms; Cloud architecture